2022
DOI: 10.1002/ece3.8571
|View full text |Cite
|
Sign up to set email alerts
|

Intra‐season variations in distribution and abundance of humpback whales in the West Antarctic Peninsula using cruise vessels as opportunistic platforms

Abstract: This is an open access article under the terms of the Creat ive Commo ns Attri bution License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(22 citation statements)
references
References 103 publications
1
20
0
Order By: Relevance
“…showed that humpback whales used the Antarctic Peninsula West (APW), Bransfield Strait West (APBSW), and Drake (APDP) Passage West SSMUs more often than expected, spending more time in a restricted behavioural state in these SSMUs. Similarly, density modelling of humpback whale sightings data likewise identifies the Bransfield Strait and northern Gerlache Strait as areas of high humpback whale abundance, at least during December (Johannessen et al, 2022). In the last decade, krill fishing has shifted spatially into the Bransfield Strait (Santa Cruz et al, 2018), representing the primary krill fishing hotspot in our analysis (Figure 5).…”
Section: Discussionsupporting
confidence: 69%
See 4 more Smart Citations
“…showed that humpback whales used the Antarctic Peninsula West (APW), Bransfield Strait West (APBSW), and Drake (APDP) Passage West SSMUs more often than expected, spending more time in a restricted behavioural state in these SSMUs. Similarly, density modelling of humpback whale sightings data likewise identifies the Bransfield Strait and northern Gerlache Strait as areas of high humpback whale abundance, at least during December (Johannessen et al, 2022). In the last decade, krill fishing has shifted spatially into the Bransfield Strait (Santa Cruz et al, 2018), representing the primary krill fishing hotspot in our analysis (Figure 5).…”
Section: Discussionsupporting
confidence: 69%
“…Baleen whale concentrations (Johnston et al, 2012) mirror these supper aggregations of krill and whales consistently distribute in these places and forage in a manner that optimises energy gain (Friedlaender et al, 2013;Friedlaender et al, 2016;Tyson et al, 2016) Johannessen et al (2022 see also Warwick-Evans et al, 2022) estimate peak potential competition (calculated as humpback whales' per capita consumption multiplied by their abundance through the season, and krill catch through the season) in April, which corresponds with the highest values in our monthly spatial overlap index. Based on the assumption that whales spend 120 days in their Southern Ocean foraging areas (Lockyer, 1981), Johannessen et al (2022) calculated very limited humpback whale-fishery competition by May, but tracking data in this study and shows that some individuals remain in the region as late as July. Further, minke whales may remain in the Western Antarctic Peninsula region much longer, and can overwinter in the area (Dominello and Širović.…”
Section: Discussionmentioning
confidence: 66%
See 3 more Smart Citations